COVID-19 Pandemic and Media in Nepal: A Thematic Analysis of the Information and Infodemic at the First Wave of SARS-Cov-2 - Pandey, Rishikesh (Dhaulagiri Journal of Sociology and Anthropology, 2025)
The infodemic of the COVID-19 pandemic throughout the globe has been reported as a new threat to the response to the pandemic, its state has not been adequately known in Nepal. This research aims to analyze the context and state of infodemic concerning the COVID-19 pandemic in Nepal, using the thematic analysis method. The news content published in Nepal during the first wave of COVID-19 pandemic has been used as data in this research. Two themes, six sub-themes, 21 code-groups, and 40 codes have been developed from the 80 pieces of sampled content. The samples of news and information were taken from purposively selected three media sources: Twitter (social media), ekantipur (print media), and online khabar (online media). The information considered for analysis was published throughout the week (08 March 2020 to 16 March 2020), within which the World Health Organization declared COVID-19 as a pandemic (11 March 2020). The results show media has disseminated some valuable information to make people aware of the pandemic, yet cases of infodemic have been notably high. Modification of the hospital’s press notes, and misuse of the Coat of Arms of the World Health Organization (WHO), United Nations Children’s Fund (UNICEF), and Government of Nepal - Ministry of Health and Population, were the most serious issues of infodemic, which misinformed even well-educated individuals. As there has been a complex information ecosystem characterized by information paradox and trust deficit, which has fundamentally altered peoples’ understanding of and response to public health emergency and making people vulnerable to long-term health problems. These findings call for a policy priority to address the issue of infodemic and reduce infodemic-related threats, thereby advancing the health system governance in Nepal.